2011
DOI: 10.1162/jocn_a_00071
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Subsecond Time Distortion in the Middle Temporal Area of Visual Cortex

Abstract: How does the brain represent the passage of time at the subsecond scale? Although different conceptual models for time perception have been proposed, its neurophysiological basis remains unknown. We took advantage of a visual duration illusion produced by stimulus novelty to link changes in cortical activity in monkeys with distortions of duration perception in humans. We found that human subjects perceived the duration of a subsecond motion pulse with a novel direction longer than a motion pulse with a repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 44 publications
6
40
0
1
Order By: Relevance
“…Indirect evidence that subjective duration is correlated with the size of the stimulus-specific neural response has been provided by Sadeghi et al (2011), who presented human participants with a sequence of 200-ms pulses of dot motion stimuli followed by a comparison pulse of variable duration. The comparison stimulus was judged longer when its direction of motion differed from the standards, and when the same stimuli were presented to monkeys (albeit while the animals performed a different task), neurophysiological recording from the middle temporal area of the visual cortex (MT/V5) revealed that the firing rate and response-duration of these neurons was greater for the oddballs than the repeats.…”
Section: Linking Repetition Suppression To Subjective Timementioning
confidence: 99%
“…Indirect evidence that subjective duration is correlated with the size of the stimulus-specific neural response has been provided by Sadeghi et al (2011), who presented human participants with a sequence of 200-ms pulses of dot motion stimuli followed by a comparison pulse of variable duration. The comparison stimulus was judged longer when its direction of motion differed from the standards, and when the same stimuli were presented to monkeys (albeit while the animals performed a different task), neurophysiological recording from the middle temporal area of the visual cortex (MT/V5) revealed that the firing rate and response-duration of these neurons was greater for the oddballs than the repeats.…”
Section: Linking Repetition Suppression To Subjective Timementioning
confidence: 99%
“…This difficulty comes from considering our results in the context of a recent study looking at repetition suppression and the oddball effect (Sadeghi et al, 2011). Recall firstly, that the oddball effect is the expansion of apparent duration of a novel stimulus presented within a train of repeated stimuli; and secondly, that repeated presentation of a stimulus suppresses the neural response associated with that stimulus (Li et al, 1993; Grill-Spector et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Sadeghi et al's (2011) study is particularly interesting because they look at the oddball effect using both human psychophysics and macaque electrophysiology. The stimulus they used, a random dot kinematogram, is a standard stimulus for driving neurons in motion area MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designados de modelos de "dependência-de-estado" devido ao facto de ancorar nas mudanças de estado das redes neuronais durante a apresentação de um estímulo; sendo essa sucessão de padrões únicos de activação uma forma de codificar o próprio tempo. Eagleman e colaboradores (Eagleman, 2008;Eagleman & Pariyadath, 2009;Pariyadath & Eagleman, 2007;Sadeghi, Pariyadath, Apte, Eagleman, & Cook, 2011) adicionaram poder explicativo (de várias ilusões temporais) a estes modelos sugerindo que a duração subjectiva também depende, da eficiência da codificação neural 17 . Por outras palavras, quanto maior for a amplitude da resposta neural (ou energia despendida) promovida pelo estímulo, durações mais longas serão percebidas.…”
Section: Eficiência De Codificação Neuralunclassified